Lipoprotein (a) Level Among Patients with Type 2 Diabetes Mellitus and Prediabetes in Comparison with Healthy Controls - Abdullah, Barhav Issa; Salih, Sherwan Ferman (Science Journal of University of Zakho, 2023)
Objective: Diabetes mellitus type 2 is a chronic endocrine condition defined as high blood glucose concentration and produced by either insulin resistance or relative lack of insulin, Prediabetes is a metabolic disorder defined by high blood glucose levels that are below the diagnostic threshold for diabetes mellitus. This study aimed to measure lipoprotein (a) levels in individuals with type 2 diabetes mellitus and prediabetic individuals. Methods: A cross-sectional research was performed at Diabetes Unit at Azadi Teaching Hospital, Kurdistan region, Iraq. The study group consist of 235 participants, 85 type 2 diabetic patients, 60 prediabetic individuals and 90 individuals as control group. Results: Mean levels of Lipoprotein (a) were higher in patients with type 2 diabetes mellitus (60.43±13.19 mg/dl) and prediabetic individuals (42.53±11.65 mg/dl) in comparison with healthy control (27.3±11.16 mg/dl). Moreover, there was higher prevalent rate of abnormal high lipoprotein (a) among type 2 diabetic patients (69 ,81.1%) and prediabetic individuals (10, 16.7%). Conclusion: High mean level of lipoprotein (a) and high prevalence rate of abnormal high lipoprotein (a) were observed in type 2 diabetic patients and prediabetic individuals.